Impact of Cybersecurity Measures on Financial Data Breaches - Grace, Joan (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to investigate impact of cybersecurity measures on financial data breaches Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that the implementation of robust cybersecurity measures effectively reduced the occurrence of financial data breaches. Through comprehensive encryption protocols and multi-factor authentication, organizations were able to enhance the security of sensitive financial information. Notably, the findings indicated a significant decline in unauthorized access attempts and instances of data leakage. Additionally, the adoption of regular security audits and employee training programs led to increased awareness and vigilance among personnel, contributing to the mitigation of potential breaches. Overall, the research demonstrated that proactive cybersecurity measures played a crucial role in safeguarding financial data and minimizing the risk of breaches. Unique Contribution to Theory, Practice and Policy: Theory of Deterrence, Diffusion of Innovation Theory and Routine Activity Theory may be used to anchor future studies on impact of cybersecurity measures on financial data breaches. Regular cybersecurity audits and vulnerability assessments should be conducted to identify weaknesses and ensure that the implemented measures remain effective against evolving threats. Policymakers should also facilitate international cooperation to combat cross-border cyber threats, fostering information sharing and coordinated response efforts.